Describing Cross-cultural Speech Behavior: A Communicative-pragmatic Field Approach; Procedia - Social and Behavioral Sciences; Vol. 154 : The XXV annual international academic conference, language and culture - Kotorova E. G. Elizaveta Georgievna (2014, 2014)
Title screen